2003
DOI: 10.1177/0890334403255643
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Education, Treatment, and Referrals by Female Physicians

Abstract: The female membership of the Mississippi State Medical Association and female physician employees of the Mississippi State Department of Health were surveyed (N = 350) to examine their practice-related decisions relative to breastfeeding; 215 (61%) responded to the survey. Discussion was commonly used for educating patients, with face-to-face demonstrations used by less than half of respondents. Female physicians with breastfeeding experience were more comfortable than others in treating sore nipples, plugged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…1999; Bernaix 2000; Guise & Freed 2000; Hellings & Howe 2000; Register et al . 2000; Arthur et al . 2003a,b; DiGirolamo et al .…”
Section: Breastfeeding Education For Practitionersmentioning
confidence: 99%
See 2 more Smart Citations
“…1999; Bernaix 2000; Guise & Freed 2000; Hellings & Howe 2000; Register et al . 2000; Arthur et al . 2003a,b; DiGirolamo et al .…”
Section: Breastfeeding Education For Practitionersmentioning
confidence: 99%
“…Embodied knowledge gained from personal experiences of breastfeeding is both powerful and influential with regard to practitioners’ knowledge, attitudes, practices and confidence in supporting breastfeeding women (Hellings & Howe 2000; Arthur et al . 2003a,b; Cantrill et al .…”
Section: Breastfeeding Education For Practitionersmentioning
confidence: 99%
See 1 more Smart Citation
“…Es handelt sich in den meisten Fäl-len um eine Infektion des Brustdrüsen-parenchyms mit Staphylococcus aureus, der meist vom Nasen-Rachen-Raum des Neugeborenen, aber auch bei mangelhafter Stillhygiene übertragen wird [1,38]. In vielen Fällen lässt sich mit einer medikamentös induzierten, temporären Funktionsruhe der Brustdrüse der Einsatz von Antibiotika vermeiden [2,21] [37] zeigten an mehr als 700 Patientinnen, dass die Serumprolaktinspiegel als Prognosefaktor für den Verlauf der Erkrankung nach erfolgter Mastektomie herangezogen werden können und dass Patientinnen mit einem postoperativ deutlich erhöhten Prolaktinspiegel ein kürze-res rezidivfreies Intervall aufweisen. Im Gegensatz dazu fanden Lissoni et al [24] bei 250 Patientinnen mit postoperativ erhöhten Prolaktinserumspiegeln eine signifikante Verlängerung des rezidivfreien Intervalls.…”
Section: Hyperprolactinemia Diagnostic and Therapeutic Aspectsunclassified
“…Further studies and surveys of medical practitioners in more recent years have reported similar results in that proactive support for breastfeeding results in better breastfeeding outcomes. A study by Arthur, Saenz and Replogle [36] of 216 female physicians found that while the majority felt comfortable discussing and treating common breastfeeding problems, they had received little training in lactation management and there was little proactive promotion of breastfeeding in their practice.…”
Section: North Americamentioning
confidence: 99%